What Factors Predict How Public Sector Projects Perform? A Review of the World Bank's Public Sector Management Portfolio - Blum, Jürgen René (World Bank, Washington, DC, 2014)
This paper uses regression analysis to identify which country context, reform content, process, and project management variables predict the performance of public sector management projects, as measured by the Independent Evaluation Group's project outcome ratings. The paper draws on data from a large sample of World Bank public sector management projects that were approved between 1990 and 2013. It contributes to an emerging literature that uses cross-country regressions to analyze public sector management reform patterns. The findings suggest that political context factors have a greater impact on the performance of public sector management projects than on other projects. Specifically, public sector management projects perform better in countries with democratic regimes than autocratic ones. They fare better in the presence of programmatic political parties and in more aid-dependent countries. Project managers' subjective risk assessments predict performance in public sector management operations better than objective risk indicators. These findings suggest that the performance of public sector management projects would benefit from a better alignment of project design with political context and from a more open dialogue about risk between task team leaders and management.